Identification of a novel variant of FOXP3 resulting in severe immune dysregulation, polyendocrinopathy, enteropathy, X‐linked syndrome highlights potential pitfalls of molecular testing. Issue 3 (22nd February 2022) - Kirchner, Allison; Sanchez, Isabelle M.; Zalan, Alice; Bhat, Gifty; Bain, Michelle
Abstract: Immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) syndrome is a rare genetic disorder that typically presents in the first year of life with severe diarrhea, autoimmune endocrine disorder, and inflammatory dermatitis, most commonly an eczematous dermatitis. IPEX syndrome is caused by variants in the FOXP3  gene leading to dysregulation of T‐regulatory (Treg) cells and an aberrant immune response. Here, we present a case of severe IPEX syndrome diagnosed following whole genome sequencing (WGS) in a 2‐week‐old boy with bloody mucoid diarrhea, failure to thrive, and a diffuse eczematous dermatitis. As multiple variants of interest were identified with WGS, this case highlights the importance of relating the clinical symptoms to the genetic results.